(untitled) (University Journal of Zoology, Rajshahi University, 2012)
Key words: Culex quinquefasciatus; Calotropis gigantea; latex; larvicidal effect. DOI: http://dx.doi.org/10.3329/ujzru.v29i1.9472 UJZRU 2010; 29(1): 77-80